Tiles with no spectra in dimension 4 - Farkas, Bálint; Szilárd Gy., Révész (MATHEMATICA SCANDINAVICA, 2006)
We show by a counterexample that the "tiling spectral" part of Fuglede’s Spectral Set Conjecture fails already in Z^4 and R^4.